Kecenderungan Kemandirian Lansia di PSTW J. Soenarti Nasution dan Pondok Lansia Tulus Kasih Kota Bandung - Lia Meilianingsih; Ghina Roshalina; Ridwan Setiawan (STIKes Karsa Husada Garut, 2018)
This research is motivated by the increasing of old population. Based on the population census in 2017, West Java including 8 large number of elderly people. Increasingly older, they will experience setbacks especially in the field of physical ability. This resulted in the occurrence of interference so as to increase dependence that requires the help of others. This study aims to determine the tendency of independence of the elderly. The research type used is descriptive, population 51 elderly, sample 34 elderly, sampling technique using nonprobability sampling type purposive sampling, research instrument using Barthel Index, Berg Balance Scale and Questionnaire Guide. Data analysis using univariate analysis followed by Run Test analysis. More than half of the dependents are partly dependent on self-reliance. Almost half of the dependents are ≥ 70 years old. More than half of the respondents had impaired immobility-related movements. Almost half of the respondents have a high fall risk associated with falling easily. The result of run test analysis showed that the three factors behind the independence of the elderly have a value of p> 0.05 which means the tendency of elderly independence caused by age factor, immobility and easy to fall. The immobility factor has the highest p value of 0.794 then it can be concluded that the factor that tends to be the background of the independence of the elderly is the most immobility factor. It is suggested to the orphanage organizer to maintain the program that has been routinely held so as to maintain the elderly conditions such as muscle strengthening exercises, flexibility and balance exercises.